SOCIAL CRITICISM IN THE SHORT STORIES MISS DURINA MAWARNI OF HARRIS EFFENDI THAHAR - Suhardi, Suhardi (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this research is to explore the social aspects contained in the short story. The research uses the method of content analysis. This qualitative research uses document techniques for data collection. Data analysis techniques, namely: (1) identifying data, (2) classifying data, (3) describing data, and (4) concluding data.Â  The results of the research obtained are the short story â€œNyonya Durina Mawarniâ€ by Harris Effendi Thahar contains social aspects in the form of (1) loss of trust (wife-husband); (2) the dilemma of an aide; and (3) social aspects related to polygamy.Â Â AbstrakTujuan penelitian ini adalah menggali aspek sosial yang terkandung dalam cerpen. Penelitian ini menggunakan metode analisis isi. Penelitian kualitatif ini menggunakan teknik dokumen untuk pengumpulan data.. Teknik analisis data, yaitu: (1) mengindentifikasi data, (2) mengklasifikasikan data, (3) mendeskripsikan data, dan (4) menyimpulkan data.Â  Hasil penelitian yang diperoleh adalah cerpen â€œNyonya Durina Mawarniâ€ karya Harris Effendi Thahar mengandung aspek sosial berupa (1) hilangnya rasa saling percaya (istri-suami); (2) dilema seorang pembantu; dan (3) aspek sosial berkaitan dengan poligami.Â